On the trail of the intangible: a theoretical and empirical investigation of innovations and patents in Germany in the years 2006-2019 - Friedrich L. Sell (International Entrepreneurship Review, 2022)
Objective: We want to better understand what incentives firms to pursue innovations. For this purpose, we set up a new intertemporal principal-agent model. We then proceed to empirically assess the determinants of innovation activities unfolded by German firms between 2006 and 2019 and to also look at the causal factors – related to innovation activities – for the occurrence of patent registration in Germany.